Anils: Photochromism by H-transfer - Hadjoudis, Eugene; Chatziefthimiou, Spyros D.; Mavridis, Irene M. (Current Organic Chemistry, 2009)
Schiff bases of salicylaldehyde with amines (anils) comprise a chemical system undergoing hydrogen-atom tautomerism between enol and keto forms and show the phenomena of solid state photochromism and thermochromism. However, the photochromic phenomenon is exhibited not only in the crystalline state but in solution and rigid glasses as well. The extensive investigations on the system converge to a general scheme, according to which upon irradiation of the enol tautomer, its electronic excited state is converted to the excited cis-keto form, which subsequently may lead either back to the enol form, or to the final photoproduct, the trans-keto form. It has been shown that photochromism is a characteristic property of the molecules and the chromo-behaviour is influenced by the environment such as the crystal packing of the compounds in the solid state and the nature of the solvent in solution. Anils, apart from their fundamental interest, have potential for applications based on their ability to change some of their properties upon irradiation, when proton transfer between the enol and the keto occurs.